State and Trends of the Carbon Market 2010 - Kossoy, Alexandre; Ambrosi, Philippe (World Bank, Washington, DC, 2013)
The carbon market endured its most challenging year to date in 2009. The global economic crisis, which started in late 2008 and intensified early in 2009, negatively impacted both the demand and supply sides of the market. As industrial output plummeted the demand for carbon assets fell. Yet even as global GDP declined by 0.6 percent in 2009, and at a more perilous rate of 3.2 percent in industrialized economies, the carbon market demonstrated resilience. The total value of the market grew 6 percent to US$144 billion ( 103 billion) by year s end with 8.7 billion tons of carbon dioxide equivalent (tCO2e) trade.